Proposal of AISC-compliant seismic design criteria for ductile partially-restrained end-plate bolted joints. (August 2019) - Tartaglia, Roberto; D'Aniello, Mario; Rassati, Gian A.
Abstract: AISC358–16 provides seismic pre-qualification rules and design procedures for fully restrained extended stiffened end-plate bolted connections, while the cases of partially restrained connections are generally not considered for seismic applications. However, provided that the failure of both bolts and the welds is prevented, partially restrained joints may exhibit satisfactory ductile behavior, also accommodating interstory drift rotation larger than 0.04 rad. This performance can be achieved if the resistance of brittle zones of the connections is greater than the ultimate resistance of the ductile components, as experimentally proved in some recent European research projects. Therefore, the study presented in this article aims at proposing design rules for partially restrained connections in order to meet the prequalification limits given by AISC358–16. To achieve this purpose, a comprehensive parametric study based on finite element analysis (FEAs) was carried out. The numerical results show that the proposed AISC-compliant procedure can guarantee satisfactory performance of partially restrained connections, which exhibit good ductility and dissipation capacity. Highlights: AISC-compliant seismic design criteria for ductile partially-restrained end-plate bolted joints are proposed. The effectiveness of the design criteria is verified by means of finite element analyses. The proposed design rules guarantee ductile behavior of the connections. The gap opening of the connection induces large membrane actions into the end-plate. Bolts should be also designed to resist the shear forces due to the membrane effects developing in the end-plate.